In-Silico Determination of Insecticidal Potential of Vip3Aa-Cry1Ac Fusion Protein Against Lepidopteran Targets Using Molecular Docking - Ahmad, Aftab; Javed, Muhammad R.; Rao, Abdul Q.; Khan, Muhammad A. U.; Ahad, Ammara; Din, Salah ud; Shahid, Ahmad A.; Husnain, Tayyab (Frontiers in Plant Science, 2015)
Study and research of Bt (Bacillus thuringiensis) transgenic plants have opened new ways to combat insect pests. Over the decades, however, insect pests, especially the Lepidopteran, have developed tolerance against Bt delta-endotoxins. Such issues can be addressed through the development of novel toxins with greater toxicity and affinity against a broad range of insect receptors. In this computational study, functional domains of Bacillus thuringiensis crystal delta-endotoxin (Cry1Ac) insecticidal protein and vegetative insecticidal protein (Vip3Aa) have been fused to develop a broad-range Vip3Aa-Cry1Ac fusion protein. Cry1Ac and Vip3Aa are non-homologous insecticidal proteins possessing receptors against different targets within the midgut of insects. The insecticidal proteins were fused to broaden the insecticidal activity. Molecular docking analysis of the fusion protein against aminopeptidase-N (APN) and cadherin receptors of five Lepidopteran insects (Agrotis ipsilon, Helicoverpa armigera, Pectinophora gossypiella, Spodoptera exigua and Spodoptera litura) revealed that the Ser290, Ser293, Leu337, Thr340 and Arg437 residues of the fusion protein are involved in the interaction with insect receptors. The Helicoverpa armigera cadherin receptor, however, showed no interaction, which might be due to either loss or burial of interactive residues inside the fusion protein. These findings revealed that the Vip3Aa-Cry1Ac fusion protein has a strong affinity against Lepidopteran insect receptors and hence has a potential to be an efficient broad-range insecticidal protein.